The effect of light levels and turbidity on human fine motor performance and visual acuity underwater - Smit, Dane Malcolm Ronald (Rhodes University, 2026)
This thesis studied the effects of light levels and turbidity on human fine motor performance and visual acuity performance underwater with 18 participants (n=18), with varying levels of underwater experience. A fine motor task and visual acuity test were compared across three light levels and three turbidity conditions, simulating commercial diving conditions at various depths and different working areas underwater. The main findings of this study were that visual acuity decreased as turbidity levels increased (p=0.000003*). Increasing light levels will increase visual acuity regardless of the water turbidity level (p=0.007599). Fine motor performance times increased despite the increase in turbidity (p= 0.001336*) and light (p=0.000936*). This shows that learning and task experience will improve fine motor task performance. This improved performance may also be attributed to a reduction of peripheral stimuli when water turbidity increases, allowing the diver to focus on the task central to their vision. Interestingly, there was no interactional effect between the light levels and water turbidity for either the fine motor task or the visual acuity task. This shows that in the presence of water turbidity, increasing light levels will improve a diver’s ability to perform fine motor tasks. There was no difference in Heart Rate Variability (HRV) between the turbidity conditions or the light levels for either task. HRV is an indicator of psychophysiological responses to stressful conditions. The lack of HRV response while submerged in the different water conditions can be attributed to the mammalian dive reflex, which reduces parasympathetic stress responses in humans and regulates heart rate (HR). the regulation of HR can reduce panic and create a state of calm when in stressful situations allowing a person to function adequately during a stressful or unnatural situation. Further studies that investigate the effects of light and turbidity underwater and the HRV response to these conditions are recommended to understand how humans can improve both performance and safety underwater, with implications for both commercial diver training protocols and operations.
Keywords: Uncatalogued